2021
DOI: 10.3390/ijerph18063108
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Experiences with Computer Simulation-Based Communication Education

Abstract: Simulation-based communication education has improved nursing students’ communication knowledge and skills. However, communication patterns that students commonly exhibit in simulated situations and students’ responses to specific clinical situations have not been systematically examined. The specific aims of the present study were (1) to identify non-therapeutic communication patterns that nursing students exhibit in simulated situations in the computer simulation-based education (ComEd) program, and (2) expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
(50 reference statements)
0
7
0
1
Order By: Relevance
“…Improved sense of self-efficacy and confidence among novice-learners were among the notable benefits of SBE exposure, as noted by Li et al (2019) as well as Abdullah Al Gharibi and Arulappan (2020) , respectively. As SBEs involve collaboration within a group, improvements in communication ( Evans et al, 2014 ;Lee et al, 2021 ;Li et al, 2019 ) and leadership ( Evans et al, 2014 ) have also been widely reported after SCE exposure. Baptista et al (2016) note that the "realism" of the SBE contributed to better participant's engagement and helped in meeting the learner's outcomes.…”
Section: Simulation-based Experiences: the Big Picturementioning
confidence: 99%
See 1 more Smart Citation
“…Improved sense of self-efficacy and confidence among novice-learners were among the notable benefits of SBE exposure, as noted by Li et al (2019) as well as Abdullah Al Gharibi and Arulappan (2020) , respectively. As SBEs involve collaboration within a group, improvements in communication ( Evans et al, 2014 ;Lee et al, 2021 ;Li et al, 2019 ) and leadership ( Evans et al, 2014 ) have also been widely reported after SCE exposure. Baptista et al (2016) note that the "realism" of the SBE contributed to better participant's engagement and helped in meeting the learner's outcomes.…”
Section: Simulation-based Experiences: the Big Picturementioning
confidence: 99%
“…As evidenced by a thorough review of the literature exploring the use of realistic, high-fidelity, computer or mannequin-based simulations improves a number of variables among learners, including skill, knowledge ( Tait et al, 2018 ), communication ( Evans et al, 2014 ;Lee et al, 2021 ;Li et al, 2019 ) and self-efficacy ( Li et al, 2019 ). As stated in the research question, the authors sought to determine how the pre-brief might contribute to these improved variables.…”
Section: Pre-brief Within the Simulation-based Experiencementioning
confidence: 99%
“…The simulator was used to dramatically decrease the unnecessary time consumption when these newly developed technologies have been applied in clinical practice. 13,14 Second, the authors demonstrated that pain was much more severe in hysteroscopy compared to vaginoscopy. Some uncertainties need clarification.…”
mentioning
confidence: 99%
“…The simulator was used to dramatically decrease the unnecessary time consumption when these newly developed technologies have been applied in clinical practice. 13,14…”
mentioning
confidence: 99%
“…La educación basada en la simulación por ordenador puede seguir cada paso del progreso de los usuarios, evaluar las actividades de aprendizaje de los usuarios durante todo el proceso de diversas maneras (grabación de voz, grabación de vídeo, etc. ), y proporcionar una retroalimentación personalizada (Lee et al, 2021).…”
Section: Estrategias Para La Educación Sobre Comunicación En Los Estu...unclassified